Filosofi Kalkulus dalam Sejarah Matematika - Nur Dina Meylaila Khasanah; Febriana, Rina (Absis: Mathematics Education Journal, 2024)
In Mathematics there are many branches of mathematics, one of which is Calculus. Calculus is often considered a difficult branch of mathematics. However, even so, Calculus is very useful in everyday life, even though we rarely realize this. Calculus greatly contributed to the development of mathematics. Not only mathematics, Calculus also contributes to the field of Physics. Looking at it from a historical perspective, Calculus has a controversial history because there are disputes between its inventors, namely Newton and Leibniz. Apart from the disputing figures, many other figures took part in this branch of Calculus. This calculus originated from the idea of calculating area by the Greek scientist Archimedes, although at that time Archimedes had not given the name calculus but he was the first to introduce the concept of calculus. From century to century, year after year the science of calculus always changes, because figures discover something new. Currently, although there are no new discoveries, the use of Calculus continues to grow from being only studied in universities to high schools. Apart from this, the use of calculus used to be simple, but now it has become more complex.